Oral Salmonella msbB Mutant as a Carrier for a Salmonella-Based Vaccine for Prevention and Reversal of Type 1 Diabetes - Cobb, Jacob; Rawson, Jeffrey; Gonzalez, Nelson; Hensel, Michael; Kandeel, Fouad; Husseiny, Mohamed I. (Frontiers in Immunology, 2021)
A therapy that includes an oral vaccine for type 1 diabetes (T1D) using live attenuated Salmonella MvP728 (ΔhtrA/ΔpurD), cytokines (IL10 and TGFβ) and preproinsulin (PPI) antigen in combination with a sub-therapeutic dose of anti-CD3 mAb was developed by our team. The vaccine combination therapy reduced insulitis and prevented and reversed diabetes in non-obese diabetic (NOD) mice. Here, we show the effectiveness of an alternative Salmonella mutant (ΔmsbB) as a carrier strain, which is anticipated to have lower risks of an inflammatory response and septicemia as a result of modification in the lipopolysaccharide (LPS) barrier via detoxification of lipid A. This mutant strain proved to have no pathogenic side effects. Salmonella mutant strain (ΔmsbB) expressed autoantigens and in combination with cytokines and anti-CD3 mAb, successfully prevented and reversed T1D to levels comparable to the other ΔhtrA/ΔpurD mutant. Additionally, the Salmonella msbB mutant resulted in higher rates of host cell infection. These results further demonstrate the potential of an oral Salmonella-based combined therapy in the treatment of early T1D.